Perception towards pedagogical agents and their effects on self- regulated learning and performance in physics among Malaysian form 4 students / Shafilla Subri, Nora Sofia Mohamed Yuran, Shahriman Zainal Abidin - Subri, Shafilla; Mohamed Yuran, Nora Sofia; Zainal Abidin, Shahriman (Institute of Research Management & Innovation (IRMI), 2012)
The purpose of this study was to investigate student perceptions toward pedagogical agents and the effects of pedagogical agents on self-regulated learning (SRL) and performance. This study employed the 4 x 2 factorial research design and the first factor was the method of instruction involving online lessons that offered four different types of agents. The second factor was student achievement based on the latest school assessment in physics. The independent variable was the types of agents chosen by the students while the dependent variables were perceptions toward the agents, levels engagement based on SRL and performance in a physics test. The sample of this study consisted of 80 Form Four science students from a rural school. The study found that there were no significant differences in learning support, friendliness, and engagement support between the agents and there were no significant differences in performance in physics by the types of pedagogical agents. For SRL, there were significant differences for the dimensions of organization and critical thinking by types of pedagogical agents but there were no significant differences for rehearsal, elaboration and meta-cognitive self-regulation.